2019
DOI: 10.1515/polyeng-2019-0120
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of SiO2 nanoparticle from bamboo leaf and its incorporation in PDMS membrane to enhance its separation properties

Abstract: Abstract A low-cost indigenous silica powder at nano-scale was synthesized by thermal combustion and alkaline extraction technique from bamboo leaf ash. The bamboo leaf ash was prepared by heating the bamboo leaf at 750°C for 5 h. The amorphous SiO2 nanoparticle with an average particle size of 20 nm was used for the industrial application. The synthesized nanoparticle as a filler was mixed with polydimethylsiloxane (PDMS) polymer solution to synthesize a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Results presented by Nair et al shows that the PDMS decomposition was completed at about 590 • C, leaving no residue [53]. Sethy et al presents TG analysis for PDMS, where the decomposition process is similar to the one obtained in our study [55]. Moreover, the authors show that the additives enhance the thermal stability of the PDMS matrix, as observed in this experiment as well.…”
Section: Thermal Analysissupporting
confidence: 87%
“…Results presented by Nair et al shows that the PDMS decomposition was completed at about 590 • C, leaving no residue [53]. Sethy et al presents TG analysis for PDMS, where the decomposition process is similar to the one obtained in our study [55]. Moreover, the authors show that the additives enhance the thermal stability of the PDMS matrix, as observed in this experiment as well.…”
Section: Thermal Analysissupporting
confidence: 87%
“…plant as source for Si. (Sethy et al, 2019) used bamboo leaf ash to prepare SiNPs and integrated them into a poly di-methyl siloxane (PDMS) membrane to increase their separation characteristics. The majority of the literature has utilized extracts of plant tissues as a support for the preparation of SiNPs in the alkaline hydrolysis step.…”
Section: Biogenic Synthesis Of Sinpsmentioning
confidence: 99%
“…38,39 Incorporating SiO 2 particles into the PDMS matrix improved the resulting mixture's thermal stability 40 by absorbing heat, thereby increasing the temperature at which the thermal degradation of the NPDMS commences. 41 Furthermore, the hydrogen bonding between SiO 2 and PDMS facilitates the increase in thermal stability of the membrane. 42 However, such beneficial effects were not significantly observed since the amount of SiO 2 on the DIW-printable NPDMS inks was very low (Figure 4b).…”
Section: Thermal Characterizationmentioning
confidence: 99%